Using elicitation mechanisms to estimate the demand for nutritious maize: Evidence from experiments in rural Ghana - Chowdhury, Shyamal; De Groote, Hugo; Meenakshi, Jonnalagadda V.; Haleegoah, Joyce; Ewool, Manfred; Banerji, Abhijit (International Food Policy Research Institute, 2013)
In this paper we assess (a) consumers’ willingness to pay (WTP) for a recently developed variety of maize that is high in provitamin A in the context of a public health intervention and (b) the performance of three elicitation mechanisms in estimating WTP in a field experiment in Ghana. The mechanisms that we used for elicitation are the Becker-DeGroot-Marschak (BDM) mechanism, kth price auction, and choice experiment. The basic design of the experiment involved random allocation of consumers to one of three elicitation methods. This was augmented to include treatment arms to address the effect of (1) participation fees and (2) nutrition information on WTP.